Understanding the Shell Passivation in Ln3+‐Doped Luminescent Nanocrystals. Issue 3 (10th March 2022) - Shi, Rui; Brites, Carlos D. S.; Carlos, Luís D.
Abstract : Shell Passivation Effect The effectiveness of shell passivation in alleviating the surface quenching in Ln 3+ ‐doped luminescent nanocrystals has long been approved, yet the understanding of passivation mechanisms remains elusive. In article number 2100194, Rui Shi, Carlos D. S. Brites, and Luís D. Carlos review the context of debates on this topic and emphasize the impacts brought by chemical disorders, which provides new perspectives for understanding the shell passivation in general cases.